Incidence of cardiac death and recurrent stent thrombosis after treatment for angiographically confirmed stent thrombosis. Issue 3 (September 2019) - Kim, Min Chul; Kim, In-Soo; Jeong, Myung Ho; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Ahn, Youngkeun; Cho, Jeong Gwan; Park, Jong Chun
Highlights: About ∼25% of patients treated for definite stent thrombosis (ST) underwent recurrent 1-year events. Incidence of 1-year cardiac death and recurrent ST were 19.3% and 5.3%, respectively. Predictors of a 1-year composite endpoint were EST, BMS ST, and STEMI). Predictors of 1-year recurrent ST were late ST and very late ST vs. EST. Abstract: Background: Although many studies showed the predictive factors of stent thrombosis (ST) occurrence, there are few data about clinical outcomes and recurrent ST after percutaneous coronary intervention (PCI) for ST. Furthermore, it is uncertain which factors can cause adverse clinical events including recurrent ST. Methods: This study examined the clinical outcomes after treatment for definite ST. Among 18, 739 patients between June 2003 and December 2016 who underwent PCI using a drug-eluting stent (DES) or bare-metal stent (BMS), 243 consecutive patients who suffered definite ST were enrolled in this study. The overall incidence of ST was 1.3% (DES 1.4% and BMS 0.8%). The study endpoint was 1-year cardiac death or recurrent definite ST after the initial ST. Results: Study endpoint occurred in 57 patients (23.5%) during the 1-year follow-up after the initial ST. In multivariate analysis, the factors predicting 1-year endpoint were early ST [adjusted hazard ratio (HR): 2.23, 95% confidence interval (CI): 1.26–4.08, p = 0.006], BMS ST (HR: 2.42, 95% CI: 1.27–4.81, p = 0.045), serum level of glucose (HR: 1.03, 95% CI: 1.01–1.05, p = 0.048), and ST-segment elevation myocardial infarction (STEMI) at the initial ST (HR: 3.73, 95% CI: 1.82–7.65, p < 0.001). Conclusions: Recurrent ST or cardiac death during the first year after the initial ST event occurred in ∼25% of patients treated for definite ST. BMS ST, serum level of glucose, STEMI, and early ST at the initial ST were associated with adverse cardiac events.